Use of Ovaprim in Ornamental Fish Aquaculture - Roy P. Yanong; Carlos Martinez; Craig A. Watson (EDIS)
FA161, an 8-page illustrated fact sheet by Roy P. E. Yanong, Carlos Martinez, and Craig A. Watson, explains for ornamental fish producers the mode of action and considerations for the use of ovaprim, a hormone product used as a spawning aid. Includes references. Published by the UF Program in Fisheries and Aquatic Sciences, School of Forest Resources and Conservation, December 2009.